2008
DOI: 10.1080/07420520802387682
|View full text |Cite
|
Sign up to set email alerts
|

Dosing Time‐Dependent Effect of Raloxifene on Plasma Fibrinogen Concentration in Ovariectomized Rats

Abstract: The chronopharmacological effect of raloxifene, a selective estrogen-receptor modulator, was evaluated by repeated dosing of ovariectomized rats. Bilateral ovariectomy or sham operation was performed at age 12 wks, and animals were kept in rooms with a 12 h light-12 h dark cycle. Raloxifene (3 mg/kg, once daily for 10 wks) or vehicle was given repeatedly at either 2 h after lights-on (2 HALO) or 14 h after lights-on (14 HALO). Plasma fibrinogen concentration at the end of the study was reduced by the drug, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…In 2001, Cushman reported that Rx appears to have more positive effects than hormone replacement therapy in lowering fibrinogen [36]. Therefore, when Rx is prescribed to postmenopausal women with osteoporosis, it is fundamental to take into consideration the dosing times in order for plasma levels not to increase to a concentration where the cardioprotective effect is lost [37]. Our findings support past reports in mice that stated that 4 months of treatment with Rx attenuates intravascular thrombosis.…”
Section: Discussionsupporting
confidence: 82%
“…In 2001, Cushman reported that Rx appears to have more positive effects than hormone replacement therapy in lowering fibrinogen [36]. Therefore, when Rx is prescribed to postmenopausal women with osteoporosis, it is fundamental to take into consideration the dosing times in order for plasma levels not to increase to a concentration where the cardioprotective effect is lost [37]. Our findings support past reports in mice that stated that 4 months of treatment with Rx attenuates intravascular thrombosis.…”
Section: Discussionsupporting
confidence: 82%
“…), timing (in reference to the wake-sleep or LD cycle), and dose/intensity of usual treatments. Research papers pertaining to chronopharmacology-administration-time (relative to the sleep-wake, menstrual, or annual cycle) differences in the pharmacokinetics and pharmacodynamics of chemical agents such as medications-are expected to state the rationale for the choice of the clock times, menstrual days, and/or months/seasons of treatment(s) (Bruguerolle, 2008;Dispersyn et al, 2008;Iurisci et al, 2009;Kawahara et al, 2008;Lemmer & Arraj, 2008;Tsuruoka et al, 2008). Finally, some research protocols may make use of special experimental designs involving forced-desynchrony, constant-routine, or timeisolation protocols, and these should be described in sufficient detail.…”
Section: Chronobiological Criteriamentioning
confidence: 99%
“…Chronomedicine is the study of the chronobiology of health and disease and the translation of applicable findings to clinical medicine (Portaluppi, 2007). In the past few years, in particular, a chronobiological approach has been extensively used in medical research, leading to a better understanding of the pathophysiological mechanisms and features of many medical conditions and public health problems (Burioka et al, 2008;Colognesi et al, 2007;Kawahara et al, 2008;Lee et al, 2008;Leibowitz et al, 2007;Leiza et al, 2007;Lin et al, 2008;Mbanu et al, 2007;Ohkura et al, 2007;Perez-Lloret et al, 2008;Sadick et al, 2007;Sallinen et al, 2008;Shah et al, 2007;Tsai et al, 2007) as well as greater insight of therapeutic issues (Boulamery et al, 2007;Bruguerolle, 2008;Coudert et al, 2008;Dispersyn et al, 2008;Dridi et al, 2008;Hermida, 2007;Hermida et al, 2007bHermida et al, , 2008Prados et al, 2007;Smolensky et al, 2007;Tsuruoka et al, 2008).…”
Section: Introductionmentioning
confidence: 99%